Motor side active power filter for induction motor - H.V. Gururaja Rao; R.C Mala; Ambika Joshi (Institute of Advanced Engineering and Science, 2020)
Power quality is an important aspect in electrical distribution and utilization systems. Variable frequency drive (VFD) controlled induction motors are widely used in industries. The output current of VFD which is nonsinusoidal is given to the induction motor. This paper proposes a motor side active power filter (MSAPF) so as to provide a pure sinusoidal current to the induction motor. An evaluation of two control strategies has been discussed in this paper i.e. Synchronous Reference Frame (SRF) theory and Instantaneous Reactive Power theory (IRPT) in the generation of the reference signal. These techniques are simulated in MATLAB/SIMULINK environment. These simulations demonstrate the reduction in total harmonic distortion (THD) in the motor current with active filter connected to the motor side.